Aluminium Phosphate Mediated Three-Component Mannich-Type Reaction - Srinivas, K.; Pratap Reddy, P.; Jayaprakash, P.; Dubey, P.K.; Kalyan Chakravarthy, A. (Asian Journal of Chemistry, 2010)
Aluminium phosphate efficiently catalyzed the one-pot, three-component Mannich-type reaction of acetophenones with aromatic aldehydes and aromatic amines under solvent-free conditions at ambient temperature and afforded the corresponding b-amino carbonyl compounds in good to excellent yields. The present methodology offers several advantages such as mild reaction conditions, shorter reaction times and simple workup procedure.